1997
DOI: 10.1006/dbio.1997.8731
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Chondroitin Sulfate Proteoglycans from Embryonic Quail That Influence Neural Crest Cell Behavior

Abstract: The movement of neural crest cells is controlled in part by extracellular matrix. Aggrecan, the chondroitin sulfate proteoglycan from adult cartilage, curtails the ability of neural crest cells to adhere, spread, and move across otherwise favorable matrix substrates in vitro. Our aim was to isolate, characterize, and compare the structure and effect on neural crest cells of aggrecan and proteoglycans purified from the tissues through which neural crest cells migrate. We metabolically radiolabeled proteoglycans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…We carefully examined the presence of various ECM components in E11.5 embryonic guts, including aggrecan, laminin α1 (LN1; LAMA1), laminin α5 (LNα5; LAMA5), collagen IV (ColIV), vitronectin (VN; VTN), FN, tenascin-W (TNW; tenascin-N -Mouse Genome Informatics) and TNC. Aggrecan, a protein sulphate proteoglycan that inhibits NCC adhesion and migration in other systems (Perris et al, 1996;Kerr and Newgreen, 1997), was not detected in E11.5 gut walls (not shown). LN1 and ColIV were present in the basal laminae around the gut epithelium, around blood vessels and at the base of the serosal layer (Fig.…”
Section: Enccs Encounter a Tnc-and Fn-rich Extracellular Environment mentioning
confidence: 94%
“…We carefully examined the presence of various ECM components in E11.5 embryonic guts, including aggrecan, laminin α1 (LN1; LAMA1), laminin α5 (LNα5; LAMA5), collagen IV (ColIV), vitronectin (VN; VTN), FN, tenascin-W (TNW; tenascin-N -Mouse Genome Informatics) and TNC. Aggrecan, a protein sulphate proteoglycan that inhibits NCC adhesion and migration in other systems (Perris et al, 1996;Kerr and Newgreen, 1997), was not detected in E11.5 gut walls (not shown). LN1 and ColIV were present in the basal laminae around the gut epithelium, around blood vessels and at the base of the serosal layer (Fig.…”
Section: Enccs Encounter a Tnc-and Fn-rich Extracellular Environment mentioning
confidence: 94%
“…If TSP-1 is directing neural crest cells into the rostral somite, it would be only one actor in a large cast of characters that influence neural crest morphogenesis. Numerous molecules concentrated in the caudal somite have been proposed to act as a barrier to neural crest cell migration, including collagen type IX (Ring et al, 1996), proteoglycans (Perris et al, 1991;Landolt et al, 1995;Henderson et al, 1997;Kerr and Newgreen, 1997), and PNA-binding glycoproteins (Oakley and Tosney, 1991;Oakley et al, 1994). Ephrins and their receptors are also expressed in patterns that are consistent with a role in inhibiting neural crest cells from the caudal somite (Krull et al, 1997;Robinson et al, 1997;Wang and Anderson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Grafting studies have shown that the selective migration of neural crest cells into the rostral somite is under regulation by factors found in the somite itself (reviewed in Erickson and Reedy, 1998). Specific factors include collagen type IX (Ring et al, 1996), versican (Landolt et al, 1995;Henderson et al, 1997), and other chondroitin sulfate proteoglycans (Perris et al, 1991;Kerr and Newgreen, 1997), as well as PNA-binding glycoproteins (Oakley and Tosney, 1991). These repulsive molecules are believed to inhibit neural crest cells from the caudal sclerotome.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are extracellular matrix (ECM) molecules: chondroitin-6-sulfate proteoglycan (CSPG), 33,34 peanut agglutinin (PNA)-binding molecules, 34,35 collagen type IX, 36 versican 37 and F-spondin. 38 T-cadherin, a cell-cell adhesion molecule, is expressed on posterior sclerotome cells.…”
Section: The Trunk Neural Crest Cellsmentioning
confidence: 99%